Antenna for humidity sensor using split ring resonator - Siti Aminah Md Akhir; Siti Zuraidah Ibrahim; Nurshamimi Rosli; Aini Syuhada Md Zain; Nurehansafwanah Khalid (Institute of Advanced Engineering and Science, 2019)
This paper presents an antenna as a humidity sensor application to control and monitor the quality of humidity. A passive sensor tag with low cost solution is suggested where it implemented on a low-cost substrate, FR4. A capacitive sensor that works from 0 to 1.5 GHz is implemented in the design. The capacitive sensor is designed based on a small antenna loaded with a Split ring resonator (SRR). To sense the humidity, the SRR resonator is coated with Kapton, placed on the top of the resonator. To validate the proposed method, a prototype was fabricated. The comparison between simulated and measured reflection coefficient is presented.